Life cycle cost, as a tool for decision making on concrete infrastructures - Matos, José C. (2018)
The use of Life Cycle Cost (LCC) tools in civil engineering is increasing, due to the need of infrastructure owners and operators to guarantee their assets maximum performance with an optimized budget. By considering these tools it will be possible to manage assets along their lifetime in a more sustainable and efficient way. Due to this reason, it was recently constituted a Task Group on fib to deal with existing LCC tools for concrete infrastructures. This paper gives an introduction to these tools, with a special emphasis to the added-value of LCC, and to the main contents of the fib TG 8.4 state-of-art technical report. This covers a description of existing LCC standards and guidelines, their applicability, the definition of different cost elements, the incorporation of risk in the analysis, etc.